Mechanical and tribological properties of electrically conductive SiC based cermets. (June 2017) - Fides, Martin; Kovalčíková, Alexandra; Hvizdoš, Pavol; Bystrický, Roman; Džunda, Róbert; Balko, Ján; Sedláček, Jaroslav
Abstract: Three different types of SiC based cermets with various content (30, 40, 50 wt.%) of electrically conductive TiNbC phase have been fabricated by hot-pressing without sintering additives. The effect of TiNbC content on the basic mechanical, electrical and tribological properties of SiC-TiNbC cermets was investigated. Tribological properties have been characterized by the ball-on-disc method at the ambient temperature and dry wear conditions with air humidity 35–40% at the load of 5–30 N, sliding distance of 500 m, with the static partner made from SiC. Corresponding wear rate was calculated and wear mechanisms were identified. Resulting materials were relatively hard, with increasing amount of TiNbC the hardness increased from 19.8 ± 1 GPa for 30 wt.% of TiNbC up to 25.4 ± 0.9 GPa at 50 wt.% of TiNbC. The fracture toughness values were independent on TiNbC phase and varied between 2.7 and 2.9 MPa.m 1/2 . Similarly, Young's modulus increased from 354 GPa to 435 GPa. It was found that electrical conductivity of SiC cermets was rapidly improved with increased fraction of metallic phases and was three orders of magnitude higher at 30 wt.% TiNbC addition and around four order of magnitude higher at 50 wt.% of TiNbC metallic phase comparing to conventional semiconductive SiC ceramics with electrical conductivity ~ 10 Sm − 1 . Coefficient of friction (between 0.3 and 0.5) and wear resistance (10 − 6 –10 − 7  mm 3 /Nm) were comparable with the wear resistant SiC materials. Highlights: Novel dense SiC/TiNbC composites were prepared without sintering additives. The electrical conductivity increased by 3–4 orders of magnitude. High hardness and wear properties comparable to that of resistant SiC retained.